Determination of in vivo and in vitro antidiabetic activity of wogonin - Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Bakhtiar, M. Taher (2016)
The present research work deals with the isolation, in vivo and in vitro antidiabetic as well as toxicological evaluation of Wogonin (5, 7-dihydroxy-8-methoxyflavone) isolated from the MeOH extract of Tetracera indica Merr. (Mempelas paya in Malay) which is traditionally used in the management of diabetes in Malaysia. Chemical investigation of the methanol extract (190 g) from the powdered leaves (1 kg) of T. indica resulted in the isolation of a desirable wogonin. Isolation of the wogonin (4.5 g) was carried out in three steps: multiple extractions with MeOH, fractionation using column chromatography (silica gel and Sephadex LH 20) and purification using recrystallization techniques with different polar solvents. Its structure was elucidated by spectroscopic analysis, mainly 1H-NMR, 13C-NMR, MASS, IR and UV techniques as well as comparison of the spectral data with those reported in the literatures. In vivo antidiabetic study of wogonin was carried out using Sprague-Dawley rats (diabetic as well as normal) at three different concentrations (1, 5 and 25 mg/kg b.w.). Wogonin at 1 mg/kg b.w. did not produce any significant anti-hyperglycemic effect. However, at 5 and 25 mg/kg b.w., wogonin was found to exhibit significant anti-hyperglycaemic activity in alloxan induced diabetic rats. In normal rats, no hypoglycaemic activity was observed at all the concentrations taken into account, when compared with +ve and –ve controlled groups. The antidiabetic activity was found to be comparable with glibenclamide (GLBC), a known oral hypoglycemic agent (5 mg/kg b.w.). In vivo toxicological study was performed using the same strain of rats at two different concentrations (5 and 25 mg/kg b.w.) for continuous 15 days. During the study period no abnormal activity and mortality were observed. Histopathology of kidney, liver and pancreas of both normal and diabetic treated rats demonstrated normal and improved condition when compared to diabetic control group. Histopathology of pancreas of diabetic rats treated with wogonin confirmed that it is helped to trigger the regeneration of beta cells in the pancreas. The present study was also carried out to evaluate the effects of wogonin on biochemical parameters such askidney functional parameter (serum urea and creatinine) and serum lipid profile (TC, TG, LDL-C and HDL-C). There were no significant changes seen in the kidney and lipid functional parameters tested. The study found out the significant efficacy of wogonin against diabetes without showing any toxicity. The in vitro antidiabetic activity investigation of the wogonin was carried out on digestive enzymes (alpha glucosidase and alpha amylase), 3T3-L1 pre-adipocytes and adipocytes. Wogonin showed less IC50 value against α-amylase in comparison to α-glucosidase. Results obtained after carrying out an α-glucosidase assay were found to be significant (p< 0.05). It was also initially subjected to cytotoxicity test against 3T3-L1 adipocytes with regard to evaluate its in vitro antidiabetic potential. Cytotoxicity test was performed through MTT assay on 3T3-L1 pre-adipocytes to determine the safe dose of the wogonin for further in vitro antidiabetic evaluation on 3T3-L1 pre-adipocytes. Wogonin was further subjected to adipogenesis to investigate insulin like activity or insulin sensitizing activity for the purpose of evaluating antidiabetic potential. Wogonin was introduced to the cells in different safe concentrations as well as in different adipogenic cocktails. The adipogenic cocktails were modified by the addition of compounds to be investigated and rosiglitazone in the presence or absence of insulin. Results vividly showed that wogonin induced adipogenesis like insulin and enhanced adipogenesis like rosiglitazone significantly. Furthermore, wogonin as well as rosiglitazone as 5 positive control were subjected to fluorescence glucose uptake test by 2-NBDG (fluorescent glucose analogue) on mature adipocytes. Results suggested significant glucose uptake activity by Wogonin and further confirm the traditional use of T. indica in the management of diabetes in Malaysia. Hence, it is concluded that ogonin is a safe and effective antidiabetic compound and may provide a chemical lead for the synthesis of new derivatives which might prove to be potential novel therapeutic agents in the treatment of diabetes. However, further in-depth research study on this compound is still warranted that might help to discover a new safe compound with strong antidiabetic activity.